The Effect Of Change Management On Organisations From An Islamic Perspective - Agustina, Putri (Journal of Business Management, 2024)
In an organisation, change is a process that cannot be avoided. The process of moving an organisation from where it is now to where it wants to be in the future is known as organisational change. To anticipate and answer future challenges, an organisation will always undergo changes. Changes in an organisation can come from outside or from within, in the form of planned or structural changes that need to be managed properly. For an organisation to progress, management is needed to facilitate the change process. Whether or not an organisation progresses has a significant impact on its success or failure. Changes in hierarchy are generally not accepted on the grounds that for every change there will be constraints. Organisational failure can be caused by organisational change; consequently, effective management is essential for progress.